Impact of the COVID-19 pandemic on cervical cancer screening in the southern city of Maranhão (Research, Society and Development, 2022)
With the COVID-19 pandemic, there was a change in the profile of priority services in the Health System, with restriction of cervical cancer screening tests. The objective of this study is to identify the impact of the COVID-19 pandemic on cervical cancer screening in a city in the south of Maranhão. This is a descriptive, cross-sectional study with a quantitative approach carried out through the collection of secondary data. Cervical cytopathological exams performed between January 2019 and February 2020 and between March 2020 and September 2021 were analyzed. According to the data obtained, the age group of women with the lowest attendance at the exams was up to 29 years old, when compared to the pre-pandemic year. It was noted that there was a significant decrease in the number of screening tests performed during the pandemic, as well as a reduction in the detection of atypia and carcinomas in cytopathological samples. It is concluded that the pandemic had a negative impact on cervical cancer screening, which can lead to late diagnoses in the future, therefore requiring the promotion of strategies that alleviate this problem.